Endothelin‐1‐induced down‐regulation of NaV1.7 expression in adrenal chromaffin cells: Attenuation of catecholamine secretion and tau dephosphorylation. Issue 7 (19th February 2013) - Nemoto, Takayuki; Yanagita, Toshihiko; Maruta, Toyoaki; Sugita, Chihiro; Satoh, Shinya; Kanai, Tasuku; Wada, Akihiko; Murakami, Manabu
Abstract : Endothelin‐1 and voltage‐dependent sodium channels are involved in control and suppression of neuropathological factors, which contribute to sculpting the neuronal network. We previously demonstrated that veratridine‐induced NaV 1.7 sodium channel activation caused intracellular calcium elevation, catecholamine secretion and tau dephosphorylation in adrenal chromaffin cells. The aim of this study was to examine whether endothelin‐1 could modulate NaV 1.7. Our results indicated that endothelin‐1 decreased the protein level of NaV 1.7 and the veratridine‐induced increase in intracellular calcium. In addition, it also abolished the veratridine‐induced dephosphorylation of tau and the phosphorylation of glycogen synthase kinase‐3β and extracellular signal‐regulated kinase. These findings suggest that the endothelin‐1‐induced down‐regulation of NaV 1.7 diminishes NaV 1.7‐related catecholamine secretion and dephosphorylation of tau. Abstract : ► Chronic treatment with endothelin‐1 (ET‐1) reduced NaV 1.7 expression. ► ET‐1 attenuated the elevation of intracellular calcium due to the reduction of NaV 1.7. ► The attenuation of intracellular calcium affected catecholamine secretion. ► ET‐1 inhibited NaV 1.7‐related dephosphorylation of tau.